Studying Cholesterol and Triglyceride Levels in Some Types of Fish in Salah Al-Din Governorate - Nuha Albassam; Faroq M. Al Habib; Saddam M. Hassan (Al-Qadisiyah Journal of Pure Science, 2021)
The study included seven common types of fish in the Iraqi local market in Salah al-Din Governorate / Tikrit, which are (Carasobarbus luteus, Alburnus mossulensis, Cyprinion kais, Chondrostoma regium, Barbus barbulus, Barbus belayewi, Barbus subquincunciatus). The study of cholesterol and triglycerides of these types of fish showed that the cholesterol levels in the experimental fish were (104.55-9.56 -6.37-9.56 -14.88-51.03-15.94) mg/100 g in the mentioned fish, respectively, and the highest level of cholesterol was in the Carasobarbus luteus fish and it reached 104.55 mg /100gm, and the lowest level in Cyprinion kais is 6.37mg/100gm. The study stated the levels of triglycerides are (990 -348 -993.5 -665.9 -703.5 -1355.2-882.2) mg/kg for fish (Carasobarbus luteus, Alburnus mossulensis, Cyprinion kais, Chondrostoma regium, Barbus barbulus, Barbus belayewi, Barbus subquincunciatus) respectively. The highest level of triglycerides is 1355.2 mg/kg. kg in Barbus belayewi fish and the lowest level in Alburnus mossulensis 348 mg/kg.